Mempertanyakan Kembali Bhinneka Tunggal Ika Di Era Post Truth Melalui Media Sosial - Parani, Rizaldi; Pramesuari, Astrid; Maldiva, Daffa Muhammad; Felicia, Edlyn (Universitas Serang Raya, 2018)
The phenomenon of post-truth appears, in which a view believed to be true is inverted and made contradictory as a new form of truth. This phenomenon appears to occur in several countries such as the United States, North Korea, the Philippines and also Indonesia. This can be seen from various actions carried out by radical organizations that question the values of Bhinneka Tunggal Ika with the desire to change these values by referring to religious values. This activity is increasingly growing in terms of followers, and further builds up on the blasphemy case accusations towards former Jakarta Governor, Basuki Tjahaja Purnama.This research focuses on how the social media has an influence in expanding the spread of hoaxes and hate speech as an effort to destabilize the values of Bhinneka Tunggal Ika. Information and data were obtained from interviews with mass organizations often labeled radical, non-governmental organizations and social observers.The results of this study confirm the need for capacity building both in the form of media literacy and also the socialization of Bhinneka Tunggal Ika values through social institutions and the Government. This is intended to create strong social capital, especially in fostering a sense of trust in the context of a pluralist society in Indonesia.Keywords: Post truth, Bhinneka Tunggal Ika, Social Media, Social Capital, Trust.